Translation Errors Made by Indonesian-English Translators in Crowdsourcing Translation Application - Salam, Zainar M; Akil, Mansur; Rahman, Andi Qashas (Universitas Negeri Makassar, 2017)
The research aims to describe the kinds of translation errors made by Indonesian-English translators in crowdsourcing translation application and the dominant kind of translation errors made by Indonesian-English translators in crowdsourcing translation application. The problem statements of the research are (1) What kinds of translation errors made by Indonesian-English translators in crowdsourcing translation application? (2) What is dominant kind of translation error made by Indonesian-English translators in crowdsourcing translation application?. The method used on the research was descriptive qualitative. The subject of the research was the Indonesian-English translators of crowdsourcing translation application. The researcher took 50 Indonesian-English translation requests (source language texts) and all of its’ translations in English (target language texts) from the crowdsourcing translation application to find out the translation errors. Then the researcher classified them into 5 kinds of translation errors. The results of the research revealed that there were 50 source language texts that translated into 353 target language texts with 350 variations of translation in total. There were 75 translation errors in total or 21.25% from all if the 353 target language texts. There were 3 (0,85%) translation errors in inversion of meaning, 11 (3.12%) translation errors in omission of meaning, 8 (2.27%) translation errors in addition of meaning, 44 (12.46%) translation errors in deviation of meaning, and 9 (2.55%) in modification of meaning. Dominant kind of the translation error that the Indonesian-English translators made was in deviation of meanings, it was more than half (58,67%) of the total translation errors.